Design and implementation of high performance field oriented control for grid-connected doubly fed induction generator via hysteresis rotor current controller - Amrane, F.; Chaiba, A.; Babes, B.E.; Mekhilef, Saad (Editura Academiei Romane, 2016)
This paper presents the design and real time implementation of a field-oriented control (FOC) for grid-connected variable speed wind turbine based on doubly fed induction generator (DFIG). The proposed method based on a hybrid Hysteresis Current (HC) with field oriented control (FOC) in order to control the rotor side converter (RSC). The grid-connected DFIG is executed using three phase locked loop (3PLL). The experimental test bench is an emulator turbine represented by direct current motor (DCM) which is coupled with the doubly fed induction generator (DFIG). The implementation is realized using dSPACE1104 card below the synchronous speed. The experimental results show high performances in steady and transient states with low THD of stator current injected to the grid (3.7 %), satisfies the IEEE harmonic standard 519 despite the variation of the references. The main advantages of this control are implementation simplicity and lower switching frequency converter.